Photochemistry for Advanced Nanoengineering: Polymer Microtubes with Inner Walls Coated with Silver Nanoparticles - Valeriy Luchnikov; Lavinia Balan (Nanomaterials and Nanotechnology)
Micro-capillaries with an engineered hidden surface were produced via the self-rolling of polymer thin films whose surface was photochemically modified so as to coat it with silver nanoparticles. The polymer films consisted of a poly(4-vinyl pyridine) (P4VP) layer topcoated with a polystyrene layer. When immersed in acid water, they underwent self-rolling due to selective swelling of the poly(4-vinyl pyridine) layer. The generation of Ag nanoparticles at the inner structure of the 40 μm-wide capillaries was carried out by a photochemically initiated reduction process. It was confirmed by UV-VIS spectroscopy, transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDX) analysis. The possibility of designing non-uniform distributions of silver particles at the inner surface of the tubes was also established. It consists of photopatterning the top of the film - the polystyrene side - prior to the swelling/selfrolling step. This approach provides new opportunities for the design of micro-compartments for micro-biological research and for micro-fluidics applications.